MULTINATIONAL CORPORATE RELATIONS IN JAPANESE COMPANY TOYOTA WITH OVERLOOK ON COOPERATION WITH PHILIPPINES (Heritage, 2020)
This paper aims to consider the issue of the special management and production model developed at Toyota, and its contribution to the development of other economies in the world, with special reference to production in the Philippines.Japan was the first country in Asia to embark on a path of modernization and as such, became a model for the surrounding countries. The Philippines is one of the countries in the Asia-Pacific region that followed the path of change and adopted the Kaizen philosophy.Japan has influenced more widely, globally, all companies in the world that strive to conduct this way of doing business in their own environment.Toyota's business philosophy and the application of kaizen as a new model of corporate governance has become synonymous with quality corporate governance around the world and has influenced the establishment of new laws in the field of economy, culture and society, in a global context.
Keywords: Japan, Philippines, Toyota, culture, economy